How to Run a Reenactment - Introduction to Reenactments and Reenactors, Part 1 - Deb Fuller (EXARC Journal)
Reenactments, meaning special events that use outside costumed interpreters, are a great way for sites to engage visitors and host memorable programs that build a following. Planning and executing a reenactment can be a daunting challenge for a site that has never hosted one. Like any special event, you have to make sure you have the staffing, resources, and logistics to handle the event. There might also be resistance from higher ups who worry about public safety and bad press from allowing outside groups to participate in programming for the site. These are legitimate issues, but they can be mitigated by solid planning and working with credible reenactors and reenactment units. The purpose of this article is to give an overview of how to plan and run a reenactment at an established historic site. There will be three parts to this article series: the first part of the article will give an overview of reenactments and reenactors in general, the second will explain what overarching questions you need to ask before and during planning your reenactment, and the last will get into the specific details of planning, logistics, marketing, and running a reenactment. Some background and caveats: I have nearly 20 years of experience in both participating in and running reenactments, but my experiences are limited to the United States. The basics of producing a reenactment are the same regardless of location but you will need to do research to find out specific details, such as laws and insurance regulations, for your own country and locality. This is important because nothing generates bad press for a site like inspectors coming in to shut down your event because you forgot to file the right permits or notify the appropriate authorities of your event. It will be hard to convince people to come out for your next event after that.